Like in Similes – A Relevance-Theoretic View - Wałaszewska, Ewa (Research in Language, 2013)
The paper examines the meaning of like as used in similes in the light of relevance theory. Similes, even though superficially indistinguishable from literal comparisons, are found to be closer to metaphors. Therefore, it is proposed that like in similes is different from like employed in literal comparisons. In particular, it is claimed that, contrary to the current relevance-theoretic position on this issue, like in similes introduces an ad hoc concept. This like is seen as both conceptual and procedural and, as such, it is distinct from both the conceptual like used in literal comparisons and the procedural like functioning as a pragmatic marker. Such a solution accounts for the similarities and differences between similes, metaphors and literal comparisons.